HVOF Deposition, comparative investigation and optimum selection of molybdenum, boron, chromium, and titanium in Iron amorphous composite coatings - Sharma, Ratnesh Kumar; Das, Randip Kumar; Kumar, Shiv Ranjan (Surface engineering, 2023)
The current investigation focuses on the comparative assessment of each alloying element such as titanium, chromium, boron, and molybdenum on mechanical and solid particle erosion behaviour of Iron amorphous composite coatings. Iron amorphous composite coatings were deposited on 316L steel. Based on mechanical and erosion properties, the ranking of the alloying element was derived using the Fuzzy analytic hierarchy process (FAHP) and Grey relational analysis (GRA). Eight different series of Iron-based composite coatings with varying alloying elements were deposited on 316L steel. The results indicated that titanium showed the maximum hardness and adhesion pull-off strength, boron showed maximum fracture toughness, Molybdenum indicated the lowest porosity and chromium indicated maximum corrosion resistance. The result of FAHP + GRA concluded that the ranking of Fe amorphous composite coatings followed the order as FeCSiMoBCr10Ti (C-2)> FeCSiMoBCr5Ti (C-1) FeCSiMo10BCrTi (C-6)> > FeCSiMo5BCrTi (C-5)> FeCSi10MoBCrTi (C-8) > FeCSiMoB10CrTi (C-4) > FeCSi5MoBCrTi (C-7) > FeCSiMoB5CrTi (C-3).